Integrasi Interkoneksi Esensi Pendidikan Islam Dalam Pembelajaran Sains - Sofia Amaliah Umroti; Nayla Zulfina Yuliandarini; Alfina Wildatul Fitriyah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
In essence, Islamic education leads humans to the path of truth so that every believer is protected from various forms of deviation. Allah SWT and the Prophet have mentioned and explained to mankind the importance of instilling everything related to Islamic education. Speaking of science, it needs to be known that a religious person will have better faith if he understands everything that exists in the universe, this means that the natural phenomena in the world are a knowledge and greatness of the Almighty God. This study aims to determine the essence of Islamic education in science learning. The research method used is library research. From this study, it was found that humans who unite the essence of Islamic education will obtain true faith, morals and morals and of course an effort in worshiping the One God. The existence of science can be a bridge or means in proving the power of Allah so that by studying science we can learn religious knowledge correctly.